SOSIALISASI PENGERJAAN SOAL UTBK DENGAN TEKNIK MATH MAGIC DI SMA NEGERI PERBATASAN KEFAMENANU - Simarmata, Justin Eduardo; Hijriani, Lailin; Wua Laja, Yosepha Patricia (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The purpose of this community service activity is to provide socialization on the work of UTBK with math magic techniques in SMAN 1 and SMAN 2 Kefamenanu. Furthermore, the background of this socialization is to improve the students' reasoning ability through familiarizing themselves with students solving non-routine problems found during the implementation of UTBK, especially in mathematics. This community service was carried out from January to March 2020 with 40 participants. This activity consists of three stages starting with the assessment of the field, the implementation phase and finally the evaluation phase. In the field assessment stage, the servant determines the participants of the socialization, which is specifically for high school students of class xii, prepares administration, prepares materials and UTBK questions and then prepares a schedule. The second stage is the implementation phase in the form of a brief exposure to the UTBK, then giving samples of the UTBK questions for students to work on and scribing questions. The last stage is the evaluation stage in the form of an evaluation of the implementation of activities that have been arranged based on each task that has been given. Based on the socialization activities that have been carried out it can be concluded that these training activities increase students' knowledge about UTBK and add student skills in working on math UTBK questions . In addition, this training motivates students to be more active in learning mathematics and to be more mature in preparing for the upcoming UTBK.